Improving the dissemination of the property information between the property advisory and the brokerage team in a real estate consultancy company - Dellosa, Romel Rey G. (Animo Repository, 2021)
The Covid-19 pandemic has forced most businesses and organizations to shift to work-from-home or remote work setups. Our real estate company had to adjust and utilize existing online communication tools and information systems to continue daily business operations. However, the inaccuracy and difficulty in using the PRIMECore, our company’s knowledge management system for property details, led to the ineffective dissemination of information among two teams within our organization. This action research focused on improving the dissemination of property information involving the Property Advisory Team and the Brokerage Team. Our action research team implemented two cycles of Coghlan’s action research method. To address the deficiencies in the PRIMECore system, our Cycle 1 intervention centered on evaluating and updating the PRIMECore through a Usability Feedback Report. We created this usability report to be used by IT in updating PRIMECore. But the unexpected resignation of IT members at the latter part of Cycle 1 made the PRIMECore no longer operational for updating. Therefore, in Cycle 2, in place of the PRIMECore, our action research team created a new centralized database for property information using Google Sheet. Our team was guided by the User Acceptability Framework and the Technology Acceptance Model (TAM) in updating the property information and in weighing the acceptability and actual usage of the new centralized database system. The data accuracy and ease of operation through the new centralized database system had improved the dissemination of property information between the Property Advisory Team and the Brokerage Team. In addition, the online and few face-to-face weekly meetings between the Property Advisory Team and the Brokerage Team that later became possible in the hybrid work set up had enhanced the information dissemination of property details between the two teams.